Occult Follicular Thyroid Carcinoma Presenting as a Frontal Bone Metastasis: A Case Report - Mahmoudreza Tahamtan; Maral Mokhtari; Sara Pakbaz; Mehdi Tahamtan (Case Reports in Medicine)
This is a rare case of metastatic follicular carcinoma of thyroid in a patient with no history of thyroid problem. A frontal bone mass was examined microscopically and showed the pattern of metastatic follicular carcinoma. Thyroid ultrasonography then revealed a nodule in left lobe. Total thyroidectomy was done for the patient and microscopic examination confirmed the diagnosis.